ICERD in Malaysian online news reports: a cross-linguistic comparative corpus analysis / Siti Aeisha Joharry and Nor Diyana Saupi - Joharry, Siti Aeisha; Saupi, Nor Diyana (Akademi Pengajian Bahasa, 2019)
The International Convention for the Elimination of Racial Discrimination (ICERD), which was not ratified in Malaysia, created a heated public discourse in the media. This cross-linguistic comparative study investigates the representation of ICERD in Malaysian news reports of two online sources in Malaysia - the widely read English portal: The Star Online, and its Malay equivalent: Berita Harian. A corpus-assisted discourse analysis was conducted to examine how news on 'IC-ERD' were reported in both English and Malay online newspapers. Initial comparative analysis of both newspapers revealed that the search term co-occurs statistically more frequently with the verb 'ratify' and its equivalent: 'meratifikasi'. Patterns indicate that 'ICERD' was mostly referring to the act of sanctioning the agreement - particularly to 'not ratify' or 'tidak akan meratifikasi', which is concurrent with the timeframe of events. Interestingly, different patterns can be found in Berita Harian (e.g. the expression of 'thanks' or gratitude of not ratifying ICERD) that are not as revealing in The Star Online reports. Some inconsistencies were also reported between the two newspapers, e.g. referring to different ministers' speech about the initial plan to ratify ICERD alongside five (The Star Online) or six (Berita Harian) other treaties in the following year.